Governing china's population - Greenhalgh, Susan (California Stanford university press, 2005)
China's giant project in social engineering has drawn worldwide attention, both because of its coercive enforcement of strict birth limits, and because of the striking changes that have occurred in China's population: one of the fastest fertility declines in modern history and a gender gap among infants that is the highest in the world. These changes have contributed to an imminent crisis of social security for a rapidly aging population, provoking concern in China and abroad.
Keywords: Winckler, Edwin A; Asian Studies; China- History; Anthropology; Comparative Politics